On the Margins: Representations of Sexual Minorities in Lithuanian Press (2000-01) - Tereškinas, Artūras (Sociologija. Mintis ir veiksmas, 2002)
This article analyzes the images of sexual minorities in the Lithuanian press during the period of January, 2000 - June, 2001. Arguing that the mass media plays a critical role in the construction of representations of the sexual minorities, the author attempts to determine whether Lithuanian press makes the issues of homosexuality and homosexual people a part of public agenda. The analysis demonstrates that sexual minorities remain a difficult topic and an extremelly sensitive issue in Lithuania. Homosexuality is frequently described as a scandal, and homosexuals are still portrayed as an underworld unfamiliar to mass population. At the end of the article, the author concludes that to correct the prejudices and misrepresentations offered by the mainstream Lithuanian press, one needs to develop alternative interpretations of homosexuality. However, to move towards non-phobic representations of lesbians and gays, it is necessary to struggle for legitimate, affirming, non-phobic inclusion of lesbians and gay men in the public sphere.